Functional Golden Brown Rice Fermentation by Monascus sp. Yellow, White Parental Strains and Their Protoplast Mutants and Fusants - Thongpradis, Panida; Trakulnaleamsai, Savitr; Pothiratana, Chetsada; Yongsmith, Busaba (Agriculture and Natural Resources, 2015)
This report points out the possibility of producing value-added fermented products from brokenmilled rice using yellow pigment-producing molds: Monascus kaoliang TISTR 3642 and its developed strains, 2 protoplast mutants (U2.3 and U2.5) and 3 fusants (F7, F10 and F43). All strains could produce yellow pigments with a single absorption peak at 370 nm, and the amount of pigment produced in depended on the pH and medium formula. Various factors affecting the growth rate, glucoamylase and yellow pigment activities of Monascus in golden-brown rice fermentation were investigated and compared among the parental strains and the five developed strains. Conditions of 38% weight per weight initial moisture content with an initial pH 5 of rice substrate, and room temperature (28–32 °C) incubation were found optimal for golden brown rice fermentation of all strains. Furthermore, their noteworthy functional properties of antioxidant activities, total phenolic compounds as well as antichoresterol agents (monacolin K) were observed and discussed.